Culture and religious in the Córrego do Bertoldo de Baixo do Município de Caratinga (MG) rural population quality of life representation - Daniele Batista Soares (2006)
lt;p align="justify"gt; The aim of the study was to understand the Córrego do Bertoldo de Baixo quality of life representation under the ethos of rural population. This is a qualitative research, case study type, made through semi-structured interview, participant observation and form, of which objective data collected were organize on the table by variables type and subgroup and analyze by SPSS program version 10.0 for Windows. On subjective data to arise four class, to Know: job, education and religious; the mankind, nature and religious; social relations, free time, leisure and religious, and last one, satisfaction life, quality of life and religious. The data show that religious was the class that arise of transversal way to others, in the ethos of rural community available, so, it is show as element strong of social identify, that to influence significantilly the building to Quality of Life representation. The religious, belief and ritual to give sense to life, to mark the job relations, nature relations, like the social relations and it catholic religious. In this study, to intend to contribute to enlargement of action and methodologic strategy used by professional teacher, non-teacher and technician on the knowledge production, to development the sensibility to several ways of the express to popular know. It believe also that, with the development to skill of listen and respect the cultural identity in the population, to arise the possibility to valorize these knows to suit the interaction between the cientific knowledge and the ways to think and act of the society.lt;/pgt;